THE IMPORTANCE OF THE WORKS OF GREAT SCIENTISTS IN THE SPIRITUAL EDUCATION OF PRIMARY SCHOOL STUDENTS - T. Еsemuratova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The main methods of ensuring national education using examples of folk oral creativity in primary grades are scientific substantiation of the formation of national and universal human qualities in students in modern educational conditions, as well as demonstration and practical substantiation of theoretical and methodological ways of their development. To scientifically and theoretically substantiate the pedagogical conditions for ensuring national education of primary school students using examples of folk oral creativity. The developed methodology for the effective organization of public education based on the study of oral folk art in primary grades can be used for the effective organization of education in general secondary schools and extracurricular institutions